The solution to the conflict between the facets of the right to know one’s parents and to be cared by them: biparentality or multiparentality? - Plácido Vilcachagua, Alex (2024)
This article examines ten cassation rulings from the Supreme Court of Justice of Peru, showing a preference for two-parenthood in paternity disputes. The decisions privilege the static identity of the child, based on his right to know his biological parents according to the ‘Convención sobre los Derechos del Niño’.Despite occasional recognition of dynamic identity, multiparenting has not been considered by the courts. The decision criteria include DNA testing and possession of family status.The article recommends that the peruvian Judicial Power consider multiparenthood as an extension of the right to identity and parental responsibility, proposing its formalization in the civil registry to benefit the best interests of the child.